2002
DOI: 10.1126/science.1068524
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum Activation Associated with Performance Change but Not Motor Learning

Abstract: The issue of whether the cerebellum contributes to motor skill learning is controversial, principally because of the difficulty of separating the effects of motor learning from changes in performance. We performed a functional magnetic resonance imaging investigation during an implicit, motor sequence-learning task that was designed to separate these two processes. During the sequence-encoding phase, human participants performed a concurrent distractor task that served to suppress the performance changes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 32 publications
12
115
2
2
Order By: Relevance
“…This corresponds with recent findings of an fMRI imaging study of a serial reaction-time task that revealed a cerebellar activation associated with the modification of motor performance but not with the learning of the visuomotor skill itself (Seidler et al 2002). Likewise, another fMRI study showed a cerebellar involvement in reassigning motor responses to different visual stimuli but not in switching attention between stimuli without motor demands (BischoffGrethe et al 2002).…”
Section: Learning Of Sequences Of Simple Visual Imagessupporting
confidence: 57%
See 1 more Smart Citation
“…This corresponds with recent findings of an fMRI imaging study of a serial reaction-time task that revealed a cerebellar activation associated with the modification of motor performance but not with the learning of the visuomotor skill itself (Seidler et al 2002). Likewise, another fMRI study showed a cerebellar involvement in reassigning motor responses to different visual stimuli but not in switching attention between stimuli without motor demands (BischoffGrethe et al 2002).…”
Section: Learning Of Sequences Of Simple Visual Imagessupporting
confidence: 57%
“…In a recent fMRI study of a serial reaction-time task, subjects performed a concurrent distractor task to suppress the performance changes associated with learning. No cerebellar activation associated with the learning phase was found, but the cerebellum seemed to contribute to the modification of motor performance after removal of the distractor (Seidler et al 2002). In the present study, to exclude a motor dependency of a potential cerebellar involvement in sequence learning, motor demands were reduced as far as possible.…”
mentioning
confidence: 99%
“…Mr. Pierson is employed by the University of Iowa. His research contribution was also supported by NIH grants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). He has no other biomedical financial interests relevant to the subject matter of this review.…”
Section: Recent Evidence For the Role Of The Cerebellum In Cognitionmentioning
confidence: 99%
“…In summary, the double role of posterior interpositus neurons as an enhancer of facial motoneuron firing and as a damping device could help to explain cerebellar contribution to the proper performance of ongoing motor responses (mainly during the acquisition process) and to its proper timing (Welsh and Harvey, 1991;Delgado-García et al, 2002;Medina et al, 2002;Seidler et al, 2002;Koekkoek et al, 2003). Trigo et al, 1999) and the corresponding eyelid position (C; in degrees) and acceleration (D; in degrees per squared second) traces.…”
Section: Phase-inversion Properties and Modulating Role Of Posterior mentioning
confidence: 99%
“…The enigmatic role of cerebellar circuits in relation to the generation and control of spontaneous and acquired motor responses has been variously ascribed to a putative center for motor coordination and integration (Eccles et al, 1967;Thach et al, 1992), a neural center controlling motor timing of the different muscles involved in a given movement (Llinás and Welsh, 1993;Welsh and Llinás, 1997;Lang et al, 1999;Kitazawa and Wolpert, 2005), the place for motor learning and memory storage (Ito, 1984;Krupa et al, 1993;Mauk, 1997;Bracha et al, 2001;Christian and Thompson, 2003) and, in a more parsimonious way, that of a center designed for the reinforcement and/or proper performance of ongoing movements (Holmes, 1939;Welsh and Harvey, 1991;Llinás and Welsh, 1993;Gruart et al, 2000;DelgadoGarcía and Gruart, 2002;Seidler et al, 2002;Jiménez-Díaz et al, 2004). Nevertheless, for a proper understanding of cerebellar functioning, it will be necessary to approach the neural activity of cerebellar circuits during the actual performance of spontaneous, reflex, and learned movements.…”
Section: Introductionmentioning
confidence: 99%